THE ROLE OF NURSING IN HYPERBARIC THERAPY ADMINISTRATION: SCOPING REVIEW - Carvalho, Ana; Castro, Carla; Alves, Sofia; Ramos, Tiago; Martins, Andreia; Moreira, Helena; Topa, Paula; Santos, Eugenia (Health and Society, 2023)
Hyperbaric oxygen therapy has evolved over time, as well as the role of nurses and is currently recommended in several treatments. Although the concept of hyperbaric oxygen therapy has received some attention, as a structural theoretical construction among different professional sectors, it was possible to verify that there are few studies carried out on the subject. This justifies the need to map and organize the studied knowledge. Thus, with this study, we intend to contribute to the knowledge of the nurse’s role in the administration of hyperbaric therapy and to reinforce their role in this context. This study has, therefore, as a starting point the following research question: “What are the nursing interventions in the use of hyperbaric therapy?”. Hyperbaric oxygen therapy, despite still having limited availability in our country, has a recognized importance in the health sector. With this review, it is hoped that a detailed analysis and clarification of the role of nurses will be possible. By mapping the respective impact in practice, it is intended to encourage future research on the subject, with a focus on improving our health services.